2020
DOI: 10.1002/erv.2716
|View full text |Cite
|
Sign up to set email alerts
|

Naturalistic outcomes for a day‐hospital programme in a mixed diagnostic sample of adolescents with eating disorders

Abstract: Despite initial data suggesting positive treatment outcomes for adolescent eating disorder day-hospital programmes (DHPs), existing studies have included limited follow-up, small samples, and a focus on restricting-type eating disorders. To address these gaps, we explored naturalistic outcomes for an adolescent eating disorders DHP. Adolescent participants (N = 265) completed measurements at treatment admission, discharge (n = 170), and various lengths of follow-up (n = 126; M follow up = 278.87 days). Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…In regard to demographics, there were no significant racial/ethnic differences between groups, however, the sample was largely comprised of young, White patients, thus, results may not be generalizable to other cultural or generational groups. Notably, there was a substantial amount of missing data at follow‐up, which is a common issue across multiple adult PHP program outcome studies of similar design (Brown et al, 2018; Reilly et al, 2020). While our data did not suggest biased attrition, we did not collect information as to why some patients did not complete the one‐month or discharge assessments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In regard to demographics, there were no significant racial/ethnic differences between groups, however, the sample was largely comprised of young, White patients, thus, results may not be generalizable to other cultural or generational groups. Notably, there was a substantial amount of missing data at follow‐up, which is a common issue across multiple adult PHP program outcome studies of similar design (Brown et al, 2018; Reilly et al, 2020). While our data did not suggest biased attrition, we did not collect information as to why some patients did not complete the one‐month or discharge assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Programming was designed based on the dialectical behavior therapy (DBT) model and guidelines for severe and complex EDs (Wisniewski, Safer, & Chen, 2007) and offered all elements of standard DBT, including DBT skills groups, individual therapy, phone coaching, and DBT consultation teams (see Brown et al, 2018 for more details). Adolescent programming used a blended family‐based therapy (FBT)‐DBT approach (see Reilly et al, 2020 for more details). In addition to DBT/FBT‐based programming, patients ate three meals and two snacks per day in program and participated in two to three other ED‐related groups per day.…”
Section: Methodsmentioning
confidence: 99%
“…A variety of alternative forms of specialised intensive care have been introduced (home treatments, day and residential care, specialised group therapies for ED subtypes/gender, etc. ; Agüera et al, 2017;Anastasiadou et al, 2020;Peckmezian & Paxton, 2020;Reilly, Rockwell, & Ramirez, 2020;Serrano-Troncoso et al, 2020).…”
Section: Day Patient and Home Treatmentmentioning
confidence: 99%
“…It is also widely reported that following DP treatment young people report reductions in a range of core eating disorder symptoms and cognitions, such as drive for thinness, shape and weight concerns and body dissatisfaction (see Table 2 ). Similarly, for those with binge/purge behaviors at assessment, reductions are reported by end of treatment ( 34 36 , 58 ).…”
Section: Resultsmentioning
confidence: 98%
“…Some programmes also offer an additional tier of intervention between DP and outpatient care. In the USA particularly it has been common to offer both a partial hospitalization program (more intensive) and an intensive outpatient program (less intensive), within the same treatment center [e.g., ( 34 , 37 , 39 , 40 , 53 )], which may be partially influenced by insurance requirements.…”
Section: Resultsmentioning
confidence: 99%